Parkinson’s disease and the effect of lexical factors on vowel articulation - Watson, Peter J. (Acoustical Society of America, 2008)
Lexical factors (i.e., word frequency and phonological neighborhood density) influence speech perception and production. It is unknown if these factors are affected by Parkinson’s disease (PD). Ten men with PD and ten healthy men read CVC words (varying orthogonally for word frequency and density) aloud while audio recorded. Acoustic analysis was performed on duration and Bark-scaled F1-F2 values of the vowels contained in the words. Vowel space was larger for low-frequency words from dense neighborhoods than from sparse ones for both groups. However, the participants with PD did not show an effect of density on dispersion for high-frequency words.